2019
DOI: 10.3389/fchem.2019.00562
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Isocyanate-Functionalized Lignins: A Key Factor for the Preparation of Lignin-Based Polyurethanes

Abstract: Using isocyanate-functionalized Kraft lignin as a reactive macromonomer for the preparation of polyurethane foams by a prepolymer technique is a well-known strategy to incorporate the biomacromolecule into a higher value polymer material. However, as of today the mechanical properties of the resulting materials are still insufficient for a number of possible applications. One reason for this limitation is that the reaction pathway and the morphological arrangement of such foams is of uttermost complexity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Indeed, some modification methods successfully converted aromatic hydroxyls into aliphatic ones, minimizing the difference in hydroxyl reactivity levels. More recently, some works reported the partial lignin functionalization with diisocyanate, in which isocyanate-functionalized lignin was developed, with high performance in foams and blend formulations [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some modification methods successfully converted aromatic hydroxyls into aliphatic ones, minimizing the difference in hydroxyl reactivity levels. More recently, some works reported the partial lignin functionalization with diisocyanate, in which isocyanate-functionalized lignin was developed, with high performance in foams and blend formulations [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive market studies confirmed the urgent demand on sustainable aromatic compounds such as lignin (and its derivatives) to substitute fossil-based aromatic substances in a wide range of applications [75,76]. Due to the aromatic character with inherent number of aliphatic and aromatic hydroxyl groups, lignins are studied as substitutes for diols and polyols for polyurethane synthesis [77][78][79][80] and preparation of phenol-based resins [81].…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive market studies confirmed the urgent demand on sustainable aromatic compounds such as lignin (and its derivatives) to substitute fossil-based aromatic substances in a wide range of applications [77,78]. Due to the aromatic character with inherent number of aliphatic and aromatic hydroxyl groups, lignins are studied as substitutes for diols and polyols for polyurethane synthesis [79][80][81][82] and preparation of phenol-based resins [83].…”
Section: Discussionmentioning
confidence: 99%